A theoretical study on the adsorption of Cr6+, Mn2+, and Pt2+ onto (8, 0) single-walled carbon nanotubes. Issue 1 (26th October 2022) - Zhang, Yan; Zhu, Zhiming; An, Libao
Abstract: The adsorption of Cr 6+, Mn 2+ and Pt 2+ ions on the (8, 0) single-walled carbon nanotube (CNT) has been investigated separately by using density functional theory calculations. Through computing the final adsorption distance, adsorption energy, and charge transfer amount, it can be concluded that the CNT is capable of adsorbing Cr 6+, Mn 2+ or Pt 2+ ions chemically. An analysis on the density of states verifies the formation of chemical bonds between the CNT and these metal ions. The decrease in energy gap of the CNT due to the adsorption of Cr 6+, Mn 2+ or Pt 2+ ions makes the adsorption systems chemically more active. The research suggests that (8, 0) single-walled carbon nanotubes could be potentially applied as sensing materials for detecting heavy metal ions or as substrates for carrying metal catalysts.